Hypoxia-preconditioned mesenchymal stem cells attenuate peritoneal adhesion through TGF-Î² inhibition - Trisnadi, Setyo; Muhar, Adi Muradi; Putra, Agung; Kustiyah, Azizah Retno (Universa Medicina, 2020)
BackgroundPeritoneal adhesions (PAs) are generally described as fibrous bands between intra-abdominal organs following an abdominal surgical operation. The definitive treatments of PAs are currently ineffective yet. Hypoxia-mesenchymal stem cells (H-MSCs) have a higher capability to survive at the site of injury than normoxia-MSCs (N-MSCs) to repair injured tissue without fibrosis. This study aimed to analyze the effect of H-MSCs in controlling formation of PAs by reducing TGF-Î² level in a rat model. Methods A study of post-test only control group design was conducted, involving eighteen PA rat models weighing 250 Â± 25 g that were randomly assigned into 3 groups, comprising control group (C), and groups T1 and T2 receiving H-MSC treatment at doses of 3 x 106 and 1.5 x 106, respectively. To induce H-MSCs, MSCs were incubated in hypoxic conditions at 5% O2 and 37oC for 24 hours. Expression level of TGF-Î² was analyzed by enzyme-linked immunosorbent assay (ELISA) at 450 nm and adhesion formation was described macroscopically. The Kruskal-Wallis variance analysis was used to analyze significant differences among the groups.ResultsThe results of this study showed that H-MSCs in group T1 inhibited TGF-Î² expression significantly on day 8 (p<0.001) and day 14 (p<0.05). Moreover, there was almost no adhesion apparent following H-MSC administration in group T1. ConclusionsBased on this study, we conclude that H-MSCs may attenuate PA formation following inhibition of TGF-Î² expression in the PA rat model.